2008
DOI: 10.1097/yco.0b013e328303ba42
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid mental and somatic disorders: an epidemiological perspective

Abstract: Although it is generally accepted that many physical conditions have been associated with serious mental disorders, the exact nature of the relationship between them is still unclear. Various factors such as unhealthy lifestyle habits, psychotropic medication, and inadequate medical treatment or provision are implicated. Further research is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 54 publications
3
40
0
1
Order By: Relevance
“…Given that psychosocial and mental health problems are strongly associated with a higher level of dependency (Scott et al, 2009), mentalphysical multimorbidity requires special attention (Bartels et al, 1999;Mercer et al, 2012). Yet, the few studies that do investigate mental-physical multimorbidity (Nuyen et al, 2006) typically focus on the association between one somatic or one psychiatric index disease and one or a restricted set of comorbid conditions (Gijsen et al, 2001;Angelelli et al, 2004;Frankenburg and Zanarini, 2004;Iacovides and Siamouli, 2008;Reijnders et al, 2008). Undeniably, the clustering of general somatic and psychiatric morbidity is hardly studied (Lobo-Escolar et al, 2008;Andrade et al, 2010), although Lobo-Escolar et al (2008) found it to be prevalent (20%) in elderly people over 55 years of age living in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Given that psychosocial and mental health problems are strongly associated with a higher level of dependency (Scott et al, 2009), mentalphysical multimorbidity requires special attention (Bartels et al, 1999;Mercer et al, 2012). Yet, the few studies that do investigate mental-physical multimorbidity (Nuyen et al, 2006) typically focus on the association between one somatic or one psychiatric index disease and one or a restricted set of comorbid conditions (Gijsen et al, 2001;Angelelli et al, 2004;Frankenburg and Zanarini, 2004;Iacovides and Siamouli, 2008;Reijnders et al, 2008). Undeniably, the clustering of general somatic and psychiatric morbidity is hardly studied (Lobo-Escolar et al, 2008;Andrade et al, 2010), although Lobo-Escolar et al (2008) found it to be prevalent (20%) in elderly people over 55 years of age living in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Such patients are deemed to be more difficult to treat and require more care, time, and frequent visits (Balanchandra et al, 2005;Kisely et al, 2006). Often, they have concurrent diagnoses (for example, substance abuse) and interrelated physical or social problems (Iacovides et al, 2008;Jones et al, 2008). General practitioners either consider these disorders too specialized for routine primary care, deeming their skills and experience inadequate for effective diagnosis and treatment, or they position themselves as complementary to specialized care, treating what are essentially physical problems (Lester et al, 2005;Lockhart, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…are known to cause an increase in the prevalence of MD. MD not only decreases the patient's quality of life but also increases morbidity and mortality due to the primary disease (33)(34)(35). For this reason, knowledge of how these drugs act and on which brain regions may help in the development of preventive strategies.…”
Section: Alexander Et Al (2010) Investigated the Effect Of P11mentioning
confidence: 99%